Decorated reduced graphene oxide transfer sulfides into sulfur and sulfone in wastewater. Issue 44 (7th October 2022) - Wang, Zheng; Cui, Hongtao; Xu, Hengduo; Sheng, Yanqing
Abstract : Sulfides cannot be completely removed using oxidation due to the production of sulfate. Abstract : Sulfides cannot be completely removed using oxidation due to the production of sulfate. In this work, a reduced graphene oxide (RGO)/Fe3 O4 hybrid material was synthesized via a simple in situ chemical method for sulfide removal. The adsorption capacity of RGO/Fe3 O4 was evaluated by sulfide removal from aqueous solution, and different experimental parameters including contact time, solution pH, adsorbent dosage, ion strength and temperature were investigated. The equilibrium data were in accordance with the Langmuir linear isotherm with a maximum uptake capacity of 173 mg g −1 . The adsorption of sulfide by the RGO/Fe3 O4 hybrid material can be attributed to the synergistic effect of both chemical and physical adsorption according to kinetic, adsorption isotherm and thermodynamic studies. The RGO/Fe3 O4 material with oxygenated functional groups could convert sulfides to stable elemental sulfur and sulfone organics. The external magnetic field could easily separate the magnetic RGO/Fe3 O4 adsorbent from the liquid. This research provides a novel strategy for the green and low-cost treatment of sulfide-containing wastewater by the RGO/Fe3 O4 hybrid material.